Contemporary world cinema : Europe, the Middle East, East Asia and South Asia - Chaudhuri, Shohini (Edinburgh University Press, 2005)
Since the start of the 1990s, despite tougher competition than ever before from Hollywood, a rebirth and flourishing of cinema has been taking place in parts of Europe, the Middle East, East Asia and South Asia. This book provides an overview of the cinemas of these regions.